Ice Giant Systems: The scientific potential of orbital missions to Uranus and Neptune. (15th October 2020) - Fletcher, Leigh N.; Helled, Ravit; Roussos, Elias; Jones, Geraint; Charnoz, Sébastien; André, Nicolas; Andrews, David; Bannister, Michele; Bunce, Emma; Cavalié, Thibault; Ferri, Francesca; Fortney, Jonathan; et al.
Abstract: Uranus and Neptune, and their diverse satellite and ring systems, represent the least explored environments of our Solar System, and yet may provide the archetype for the most common outcome of planetary formation throughout our galaxy. Ice Giants will be the last remaining class of Solar System planet to have a dedicated orbital explorer, and international efforts are under way to realise such an ambitious mission in the coming decades. In 2019, the European Space Agency released a call for scientific themes for its strategic science planning process for the 2030s and 2040s, known as Voyage 2050 . We used this opportunity to review our present-day knowledge of the Uranus and Neptune systems, producing a revised and updated set of scientific questions and motivations for their exploration. This review article describes how such a mission could explore their origins, ice-rich interiors, dynamic atmospheres, unique magnetospheres, and myriad icy satellites, to address questions at the heart of modern planetary science. These two worlds are superb examples of how planets with shared origins can exhibit remarkably different evolutionary paths: Neptune as the archetype for Ice Giants, whereas Uranus may be atypical. Exploring Uranus' natural satellites and Neptune's captured moon Triton could reveal how Ocean Worlds form and remain active, redefining the extent of the habitable zone in our Solar System. For these reasons and more, we advocate that an Ice Giant System explorer should become a strategic cornerstone mission within ESA's Voyage 2050 programme, in partnership with international collaborators, and targeting launch opportunities in the early 2030s.